Level of Smoking Addiction and Affecting Factors in Nursing Students Hemşirelik Öğrencilerinin Sigara Bağımlılık Düzeyi ve Etkileyen Faktörler - Beyaz, Emine; Gökçeoğlu, Sonay (My University, 2022)
Aim: This study aims to determine the smoking and nicotine addiction levels and their affecting factors among nursing students. Materials and Methods: The study was conducted between November and December 2019, with 247 nursing students who agreed to participate in the study. The data were collected using an introductory information form and the Fagerström test for nicotine dependence. The data were evaluated using the chi-square test, one of the descriptive and univariate analyses, and analyzed using the Statistical Package for the Social Sciences 20.0 software. Results: Of the nursing students, 61.9% were female. The males (38.3%) had higher levels of smoking than the females. Those aged 21 years and above (12.1%) had higher levels of smoking than those between 17-20 years of age (p<0.05). In addition, the first-year students (8.0%) had lower levels of smoking than other students. Cigarette use was lower in nursing students who knew the harms of smoking (18.6%) compared to those who did not know (p<0.05). It was higher in those who had retaken a failed course and in those who had a smoker in their family (25.3%) or friend circle (24.9%) (p<0.05). Education and other smoking characteristics had no effect on smoking status (p>0.05). Of the nursing students who smoked, 92.9% had a very advanced level of nicotine addiction. Conclusion: Smoking status is negatively affected by being male, age, retaking a failed course, having a friend who is a smoker, having a smoker in the family, and considering smoking as harmless to health.